PEMANFAATAN FACE TONER EKSTRAK DAUN BINAHONG (Anredera Cordfolia (TEN) Steenis) SEBAGAI PERAWATAN KULIT BERJERAWAT - Dini Hidayah Hutabarat; Prima Minerva (Lembaga Yasin AlSys, 2026)
Acne is one of the most common skin problems experienced by adolescents and adults and may reduce self-confidence. One natural ingredient with potential for use in acne skin care is binahong leaf extract (Anredera cordifolia), which is known to contain flavonoids and saponins that function as antibacterial and anti-inflammatory agents and help cleanse the skin of dirt and excess oil. This study aimed to formulate a face toner containing binahong leaf extract for acne-prone skin, as evaluated through laboratory, organoleptic, and hedonic tests. The study employed a quantitative descriptive approach with an experimental design. The data consisted of primary data obtained through observation, documentation, and questionnaires, while the organoleptic and hedonic tests involved seven trained panelists. The data were analyzed using descriptive percentage analysis. The face toner was formulated in three concentrations: F1 (2.5%), F2 (5%), and F3 (7.5%). Physical quality evaluation was conducted through laboratory tests, including flavonoid and saponin content, pH, homogeneity, and drying time, as well as organoleptic tests covering texture, color, and aroma, and hedonic tests assessing the panelists’ degree of preference. The results showed that the binahong leaf extract face toner contained flavonoids and saponins, had a pH within the standard range (4.5–6.5), demonstrated homogeneity across all formulations, and exhibited a drying time of less than 1 minute in formulation F1. Based on the organoleptic and hedonic tests, formulation F2 was the most preferred by the panelists. Therefore, binahong leaf extract can be utilized in the formulation of cosmetic face toner for acne-prone facial skin and has the potential to serve as a natural alternative for skin care.